Multi-level quality improvement strategies to optimize HPV vaccination starting at the 9-year well child visit: Success stories from two private pediatric clinics - Sherri Zorn; Gabrielle Darville - Sanders; Thuy Vu; Amy Carter; Katie Treend; Char Raunio; Anjali Vasavada (Taylor & Francis Group, 2023)
HPV vaccination rates remain far below goal, leaving many adolescents unprotected against future HPV-related cancers. Starting HPV vaccine at age 9 may improve timely preteen vaccination. The "HPV Vax at 9" Quality Improvement intervention paired HPV vaccination with 9- and 10-year well child visits and was piloted at two pediatric clinics (n = 9 sites) in Washington between 2018 and 2022. Supporting interventions included standardized immunization schedule posters in exam rooms, electronic medical record supports, provider and staff training, strong provider recommendations, printed educational resources, and peer-to-peer champion coaching. Provider and clinic acceptance was high with HPV vaccine administration occurring at 68-86% of the 9- and 10-year well child visits. During the first year, HPV initiation rates at age 9-10 increased by 30 percentage points or more at each clinic. Sustained improvements in initiation and series completion were seen with completion at age 11-12 rising as much as 40 percentage points from 22 to 62%. Downward pressure of the COVID-19 pandemic on HPV vaccination rates was mitigated. Pairing HPV vaccine with 9- and 10-year well child visits, posting the standardized immunization schedule, and instituting EMR supports for HPV at 9 may be effective and sustainable strategies to simplify clinic workflows and increase timely HPV vaccination.